2020
DOI: 10.1177/1475921720945195
|View full text |Cite
|
Sign up to set email alerts
|

Rapid localization of acoustic source using sensor clusters in 3D homogeneous and heterogeneous structures

Abstract: The acoustic source localization in 3D structures is a challenging task especially if the structure is heterogeneous. A large number of unknown parameters in a 3D heterogeneous structure require a large number of sensor arrays for accurate source localization. In this article, a localization technique is proposed using triangular pyramid shaped sensor clusters. The time difference of arrival of acoustic signals between different sensors of the clusters is analyzed to localize the acoustic source. It uses acous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Up to now, a lot of work has been done by using the Lamb wave for damage evaluation and monitoring. Aimed at detecting unknown damage in three-dimensional heterogeneous structures, a localization is proposed by Yin et al [9]. This technique helps to localize the acoustic source with only a few sensors, which is heuristic for the scenario that limited sensors can be used for the monitoring of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a lot of work has been done by using the Lamb wave for damage evaluation and monitoring. Aimed at detecting unknown damage in three-dimensional heterogeneous structures, a localization is proposed by Yin et al [9]. This technique helps to localize the acoustic source with only a few sensors, which is heuristic for the scenario that limited sensors can be used for the monitoring of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Kundu’s technique places three sensors in an L-shape to predict the location of the acoustic source. This technique can be used for complex inhomogeneous structures [ 21 ], highly anisotropic structures [ 22 ], and three-dimensional structures [ 23 ]. Wu et al [ 24 ] and Yin et al [ 25 ] suggested various sensor placement alternatives in cluster geometries to achieve more flexibility and/or more accurate predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Another ASL technique in highly anisotropic plates using ‘‘L’’-shaped sensor clusters was proposed by Park et al 28 and Sen et al 29,30 using wavefront shapes. Yin et al 31,32 extended applications of “L”-shaped sensor clusters to two- and three-dimensional heterogeneous structures.…”
Section: Introductionmentioning
confidence: 99%